A TiO2-P photocatalytic material derived from NH2-MIL-125(Ti), its preparation method and application
Patent Information
- Application Number
- CN202611032702.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]Zhang等人采用连续离子层吸附反应法使硒化镉纳米颗粒在高长径比的二氧化钛纳米线阵列(TNWAs)上原位生长,形成CdSe/TNWAs 异质结催化剂,CdSe/TNWAs体系对混合污染物的总降解效率在4小时内达到99.4%,结果还表明所开发器件具有良好的稳定性,可应用于复杂工作环境,但降解时间太长,所需的能耗较大(Nano Energy, 2025, 136:110762)
本发明的由NH2-MIL-125(Ti)衍生的TiO2-P光催化材料,依托前驱体继承的多级多孔骨架、高比表面积与可调表面电子结构形成独特反应界面机理,其一,发达贯通孔道可同步吸附抗生素与染料两类有机分子,缩短污染物向催化活性位点的传质距离;材料受光照激发后产生光生电子-空穴对,经界面能带调控有效抑制载流子复合,生成OH、
O2-等强氧化性活性自由基,可同步进攻抗生素官能团与染料共轭发色基团,逐步破坏有机分子骨架并完全矿化为CO2、H2O等无毒产物,避免有毒致癌中间产物富集;其二,针对水体中SO42-、Cl-、Ca2+、Mg2+等无机离子抑制机理,该材料特殊孔道限域效应可阻隔大量无机离子直接占据内部活性位点,同时表面修饰调控电子分布,削弱阴离子对氧化自由基的淬灭反应、阳离子对界面电荷传输的阻滞作用,从微观反应层面大幅提升体系耐离子干扰性能;其三,本发明制备的TiO2-P相比传统TiO2具有更大的比表面积,增加了对可见光的利用率,缩短了禁带宽度;所制备的TiO2-P光催化材料化学稳定性好、成本低廉,实现抗生素-染料复合污染物同步深度矿化,有效消解复杂水体无机离子对降解反应的抑制作用;且制备工艺简单,以太阳能激发氧化还原反应,无需持续投加氧化剂、絮凝药剂,在降解抗生素与染料混合污水等方面兼具绿色低碳与稳定、高效的反应优势。
Smart Images

Figure CN122894973A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional materials technology, and relates to photocatalytic materials, specifically to a TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) and its preparation method and application. Background Technology
[0002] Pharmaceutical production and dyeing are significant sources of industrial water pollution. Wastewater from these two industries commonly carries antibiotics and dyes, forming typical antibiotic-dye complex water pollution that poses a persistent and serious threat to the balance of aquatic ecosystems and human health. Antibiotics remaining in water bodies are highly toxic, biologically stable, and difficult to degrade naturally. Their long-term retention in the aquatic environment can easily induce the development of drug-resistant genes in microorganisms, accelerate the spread of drug-resistant bacteria, disrupt the aquatic ecosystem, and trigger potential public health and safety risks. Dyes, on the other hand, have stable molecular structures and high water color, which not only block sunlight and inhibit photosynthesis in aquatic organisms, but their degradation process also produces intermediate byproducts that pose teratogenic, carcinogenic, and mutagenic risks, exhibiting significant biotoxicity.
[0003] In actual industrial wastewater and natural aquatic environments, antibiotics and dyes do not exist independently, but rather are mixed and coexist synergistically, significantly increasing the difficulty of pollutant degradation and transformation, and adding complexity to water pollution control. Meanwhile, SO4 is widely present in the aquatic environment. 2- Cl - Mg 2+ K + NO 3- Ca 2+ Inorganic ions, such as those that occupy active sites in catalytic materials and quench active free radicals in the system, can significantly inhibit the efficient degradation of pollutants and greatly reduce the treatment efficiency and stability of water treatment processes. This is one of the main difficulties in the actual treatment of complex water pollution.
[0004] Currently, the industry mainly uses traditional water treatment processes such as adsorption and biological treatment. These technologies can only achieve preliminary removal of pollutants and are difficult to completely mineralize complex pollutants such as antibiotics and dyes. They have problems such as incomplete pollutant removal and a high risk of secondary pollution. At the same time, traditional processes have weak resistance to inorganic ion interference, and their treatment effect is greatly reduced in actual wastewater systems with complex ion coexistence. They cannot meet the stringent requirements of current industrial wastewater deep treatment, compliance with discharge standards, and ecological water body restoration.
[0005] Photocatalysis technology, with its advantages of being able to drive reactions using solar energy, thorough degradation, and no secondary pollution, has become one of the core technologies for efficient water pollution control. It can achieve deep degradation and mineralization of organic pollutants and has broad application prospects in the treatment of complex polluted water bodies.
[0006] Zhang et al. used a continuous ion-layer adsorption reaction method to grow cadmium selenide nanoparticles in situ on high aspect ratio titanium dioxide nanowire arrays (TNWAs), forming a CdSe / TNWAs heterojunction catalyst. The total degradation efficiency of the CdSe / TNWAs system for mixed pollutants reached 99.4% within 4 hours. The results also showed that the developed device has good stability and can be applied to complex working environments, but the degradation time is too long and the energy consumption is relatively large (Nano Energy, 2025, 136:110762). Liu et al. designed a photocatalytic synergistic persulfate activation CDs-BiO1-xCl / PS system. This system can work under both dark and visible light conditions to achieve all-weather degradation of pollutants, and the degradation rate of the system is minimally affected by the coexistence of ions, indicating that the catalyst has excellent anti-interference ability. However, the preparation cost is high, which is not conducive to large-scale preparation (Water Research, 2010, 282(000):12). Yang et al. designed a novel oxygen-vacancy-rich S-type MoO3-x@MoS2 heterojunction material, which significantly improved water purification efficiency through photo-induced peroxymonosulfate (PMS) activation. The system exhibited excellent resistance to interference from coexisting ions and wide pH adaptability (3-11), and maintained a degradation efficiency of over 86% in actual water bodies. However, the preparation process was cumbersome (Chemical Engineering Journal, 2026:176697).
[0007] In summary, existing technologies lack systematic research on the synchronous degradation mechanism and synergistic transformation law of antibiotic-dye composite pollutants in actual aquatic environments, as well as the response mechanism, performance degradation mechanism and regulation strategy of catalytic materials in complex inorganic ion coexistence systems. The high cost of material preparation and operation and maintenance makes it difficult to support the large-scale application of photocatalysis technology in the deep treatment of actual industrial composite wastewater. Summary of the Invention
[0008] To address the shortcomings of existing technologies, the present invention aims to provide a TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) that exhibits high photocatalytic activity, good chemical stability, low cost, and simple preparation method, as well as its preparation method and applications, capable of degrading antibiotic-dye complex and ion-coexisting pollutants.
[0009] To achieve the above objectives, the present invention employs the following technical solution: A method for preparing a TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) includes the following steps: S1. Using N,N-dimethylformamide and methanol in a volume ratio of 1:1 as solvents, mix them evenly by stirring. Add polyvinylpyrrolidone and 2-aminoterephthalic acid to the mixed solvent in a mass ratio of (0.05~0.5):1, wherein the total mass of polyvinylpyrrolidone and 2-aminoterephthalic acid to the volume ratio of the solvent is (0.004~0.05):1 g / mL. After complete dissolution, add tetrabutyl titanate to a concentration of 0.01~0.2 mol / L, continue stirring for 180 min, then transfer the solution to a Teflon liner, place it in an oven at 200~500℃ for hydrothermal reaction for 10~40 h, collect the product by centrifugation, and dry it to obtain NH2-MIL-125(Ti). S2. The dried NH2-MIL-125(Ti) was placed in a muffle furnace and calcined in air at 300~650℃ for 2~8h to finally obtain the NH2-MIL-125(Ti) derived TiO2 photocatalytic material, named TiO2-P.
[0010] The present invention also has the following technical features: Preferably, the drying in step S1 is vacuum drying at 60°C for 8-12 hours.
[0011] Preferably, the heating rate of the muffle furnace in step S2 is 1~10℃ / min.
[0012] This invention also protects a TiO2-P photocatalytic material prepared by the NH2-MIL-125(Ti) derivatization method as described above, and its application in the photocatalytic degradation of antibiotic-dye complex pollutants and ion coexisting pollutants in wastewater.
[0013] Compared with the prior art, the present invention has the following technical effects: The TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) of this invention relies on the multi-level porous framework, high specific surface area, and tunable surface electronic structure inherited from the precursor to form a unique reaction interface mechanism. Firstly, the well-developed interconnected channels can simultaneously adsorb both antibiotics and dyes, shortening the mass transfer distance of pollutants to the catalytically active sites. Secondly, after the material is excited by light, it generates photogenerated electron-hole pairs, which, through interface bandgap modulation, effectively suppress carrier recombination, generating… OH、 O 2-The highly reactive free radicals can simultaneously attack the functional groups of antibiotics and the conjugated chromophores of dyes, gradually destroying the organic molecular skeleton and completely mineralizing it into non-toxic products such as CO2 and H2O, thus avoiding the accumulation of toxic and carcinogenic intermediates; secondly, it targets SO4 in water bodies. 2- Cl - Ca 2+ Mg 2+ The material employs an inorganic ion suppression mechanism, where the unique pore confinement effect prevents a large number of inorganic ions from directly occupying internal active sites. Simultaneously, surface modification regulates electron distribution, weakening the quenching reaction of anions on oxidative free radicals and the blocking effect of cations on interfacial charge transport, significantly improving the system's resistance to ion interference at the microscopic reaction level. Thirdly, the TiO2-P prepared in this invention has a larger specific surface area than traditional TiO2, increasing the utilization rate of visible light and shortening the band gap. The prepared TiO2-P photocatalytic material exhibits good chemical stability and low cost, achieving simultaneous deep mineralization of antibiotic-dye composite pollutants and effectively eliminating the inhibitory effect of inorganic ions in complex water bodies on the degradation reaction. Furthermore, the preparation process is simple, using solar energy to excite redox reactions without the need for continuous addition of oxidants or flocculants, combining green, low-carbon, stable, and highly efficient reaction advantages in the degradation of mixed antibiotic and dye wastewater. Attached Figure Description
[0014] Figure 1 This is a scanning electron microscope (SEM) image of the TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) prepared in Example 1 of this invention; Figure 2 The image shows the recycling performance of the TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) prepared in Example 1 of this invention. Figure 3 The image shows the photocatalytic performance of ciprofloxacin on TiO2-P photocatalyst material derived from NH2-MIL-125(Ti) prepared in Example 1 of this invention. Figure 4-9 This is the ultraviolet spectrum of the TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) prepared in Example 2 of this invention for mixed pollutants; Figure 10 This is a graph showing the photocatalytic performance of the TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) prepared in Example 3 of this invention for coexisting ions. Detailed Implementation
[0015] The present invention will be further described in detail below with reference to specific embodiments. These descriptions are for explanation purposes only and are not intended to limit the scope of the invention.
[0016] The polyvinylpyrrolidone used in the following examples is PVP K30, with an average molecular weight of 51,000.
[0017] Example 1 S1. Mix 25 mL of N,N-dimethylformamide (DMF) and 25 mL of methanol thoroughly by stirring. Add 1.812 g of 2-aminoterephthalic acid to the mixed solvent to make the concentration of 2-aminoterephthalic acid 0.20 mol / L. Then add 1.426 mL of tetrabutyl titanate to make the concentration of tetrabutyl titanate 0.10 mol / L. Then add 0.544 g of polyvinylpyrrolidone (K30) and continue stirring for 180 minutes. Then transfer the solution to a Teflon liner and place it in an oven for hydrothermal treatment at 200℃ for 20 h. Collect the product by centrifugation and dry it under vacuum at 60℃ for 10 h to obtain NH2-MIL-125(Ti). S2. Take 0.4g of dried NH2-MIL-125(Ti) and heat it to 400℃ in a muffle furnace at a heating rate of 2℃ / min. The calcination time is 5 h, and finally TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) is obtained.
[0018] like Figure 1-3 The images show scanning electron microscope (SEM) images, UV-Vis absorbance curves, and recycling performance diagrams of the TiO2-P photocatalyst material prepared by this method. Figure 1 It can be seen that its shape is a typical round disc. Figure 2 It can be seen that the absorbance of the TiO2-P photocatalytic material extends to 448 nm, thus broadening the absorption range of the photocatalyst. Figure 3 It can be seen that the cycle efficiency of TiO2-P photocatalytic material did not decrease significantly, indicating that the photocatalytic cycle degradation efficiency of TiO2-P photocatalytic material is very stable.
[0019] Example 2 S1. Mix 40 mL of N,N-dimethylformamide (DMF) and 40 mL of methanol thoroughly by stirring. Add 1.449 g of 2-aminoterephthalic acid to the mixed solvent to make the concentration of 2-aminoterephthalic acid 0.10 mol / L. Then add 0.913 mL of tetrabutyl titanate to make the concentration of tetrabutyl titanate 0.04 mol / L. Then add 0.290 g of polyvinylpyrrolidone (K30) and continue stirring for 180 minutes. Then transfer the solution to a Teflon liner and place it in an oven for hydrothermal treatment at 200℃ for 20 h. Collect the product by centrifugation and dry it under vacuum at 60℃ for 10 h to obtain NH2-MIL-125(Ti). S2. Take 0.4g of dried NH2-MIL-125(Ti) and heat it to 400℃ in a muffle furnace at a heating rate of 2℃ / min. The calcination time is 5 h, and finally TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) is obtained.
[0020] like Figure 4-9 The image shows the UV spectrum of the TiO2-P photocatalyst material prepared by this method for mixed pollutants. Figure 4-9 It can be seen that TiO2-P photocatalytic materials have good degradation performance for antibiotic-antibiotic mixed solutions, antibiotic-dye mixed solutions, and dye-dye mixed solutions.
[0021] Example 3 S1. Mix 25 mL of N,N-dimethylformamide (DMF) and 25 mL of methanol thoroughly by stirring. Add 1.087 g of 2-aminoterephthalic acid to the mixed solvent to make the concentration of 2-aminoterephthalic acid 0.10 mol / L. Then add 1.711 mL of tetrabutyl titanate to make the concentration of tetrabutyl titanate 0.10 mol / L. Then add 0.544 g of polyvinylpyrrolidone (K30) and continue stirring for 180 minutes. Then transfer the solution to a Teflon liner and place it in an oven for hydrothermal treatment at 200℃ for 24 h. Collect the product by centrifugation and dry it under vacuum at 60℃ for 10 h to obtain NH2-MIL-125(Ti). S2. Take 0.5g of dried NH2-MIL-125(Ti) and heat it to 550℃ in a muffle furnace at a heating rate of 1.5℃ / min. The calcination time is 3 h, and finally TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) is obtained.
[0022] like Figure 10 The image shows the photocatalytic performance of the TiO2-P photocatalytic material prepared by this method for coexisting ions. Figure 10 It can be seen that TiO2-P photocatalytic material has good degradation performance for antibiotics containing different inorganic ions.
[0023] Example 4 S1. Mix 60 mL of N,N-dimethylformamide (DMF) and 60 mL of methanol thoroughly by stirring. Add 0.870 g of 2-aminoterephthalic acid to the mixed solvent to make the concentration of 2-aminoterephthalic acid 0.04 mol / L. Then add 0.952 mL of tetrabutyl titanate to make the concentration of tetrabutyl titanate 0.028 mol / L. Then add 0.174 g of polyvinylpyrrolidone (K30) and continue stirring for 180 minutes. Then transfer the solution to a Teflon liner and place it in an oven at 200℃ for hydrothermal treatment for 20 h. Collect the product by centrifugation and dry it under vacuum at 60℃ for 8 h to obtain NH2-MIL-125(Ti). S2. Take 0.5g of dried NH2-MIL-125(Ti) and heat it to 500℃ in a muffle furnace at a heating rate of 1.5℃ / min. The calcination time is 3 h, and finally TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) is obtained.
[0024] Example 5 S1. Mix 20 mL of N,N-dimethylformamide (DMF) and 20 mL of methanol thoroughly by stirring. Add 1.087 g of 2-aminoterephthalic acid to the mixed solvent to make the concentration of 2-aminoterephthalic acid 0.15 mol / L. Then add 1.027 mL of tetrabutyl titanate to make the concentration of tetrabutyl titanate 0.09 mol / L. Then add 0.435 g of polyvinylpyrrolidone (K30) and continue stirring for 180 minutes. Then transfer the solution to a Teflon liner and place it in an oven for hydrothermal treatment at 200℃ for 20 h. Collect the product by centrifugation and dry it under vacuum at 60℃ for 10 h to obtain NH2-MIL-125(Ti). S2. Take 0.5g of dried NH2-MIL-125(Ti) and heat it to 550℃ in a muffle furnace at a heating rate of 1.5℃ / min. The calcination time is 3h, and finally TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) is obtained.
[0025] Example 6 S1. Mix 25 mL of N,N-dimethylformamide (DMF) and 25 mL of methanol thoroughly by stirring. Add 1.630 g of 2-aminoterephthalic acid to the mixed solvent to make the concentration of 2-aminoterephthalic acid 0.18 mol / L. Then add 2.304 mL of tetrabutyl titanate to make the concentration of tetrabutyl titanate 0.162 mol / L. Then add 0.408 g of polyvinylpyrrolidone (K30) and continue stirring for 180 minutes. Then transfer the solution to a Teflon liner and place it in an oven at 300℃ for hydrothermal treatment for 20 h. Collect the product by centrifugation and dry it under vacuum at 60℃ for 10 h to obtain NH2-MIL-125(Ti). S2. Take 1g of dried NH2-MIL-125(Ti) and heat it to 350℃ in a muffle furnace at a heating rate of 3.5℃ / min. The calcination time is 3.5 h, and finally TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) is obtained.
[0026] Example 7 S1. Mix 50 mL of N,N-dimethylformamide (DMF) and 50 mL of methanol thoroughly by stirring. Add 0.362 g of 2-aminoterephthalic acid to the mixed solvent to make the concentration of 2-aminoterephthalic acid 0.02 mol / L. Then add tetrabutyl titanate to make the concentration of tetrabutyl titanate 0.2 mol / L. Then add 0.029 g of polyvinylpyrrolidone (K30) and continue stirring for 180 minutes. Then transfer the solution to a Teflon liner and place it in an oven for hydrothermal treatment at 400℃ for 40 h. Collect the product by centrifugation and dry it under vacuum at 60℃ for 8 h to obtain NH2-MIL-125(Ti).
[0027] S2. Take 1.5g of dried NH2-MIL-125(Ti) and heat it to 300℃ in a muffle furnace at a heating rate of 1℃ / min. The calcination time is 8 h, and finally TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) is obtained.
[0028] Example 8 S1. Mix 100 mL of N,N-dimethylformamide (DMF) and 100 mL of methanol thoroughly by stirring. Add 1.812 g of 2-aminoterephthalic acid to the mixed solvent to make the concentration of 2-aminoterephthalic acid 0.05 mol / L. Then add 0.57 mL of tetrabutyl titanate to make the concentration of tetrabutyl titanate 0.01 mol / L. Then add 0.272 g of polyvinylpyrrolidone (K30) and continue stirring for 180 minutes. Then transfer the solution to a Teflon liner and place it in an oven for hydrothermal treatment at 500℃ for 10 h. Collect the product by centrifugation and dry it under vacuum at 60℃ for 12 h to obtain NH2-MIL-125(Ti). S2. Take 2g of dried NH2-MIL-125(Ti) and heat it to 650℃ in a muffle furnace at a heating rate of 10℃ / min. The calcination time is 2 h, and finally TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) is obtained.
[0029] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a TiO2-P photocatalytic material derived from NH2-MIL-125(Ti), characterized in that, Includes the following steps: S1. Using N,N-dimethylformamide and methanol in a volume ratio of 1:1 as solvents, mix them evenly by stirring. Add polyvinylpyrrolidone and 2-aminoterephthalic acid to the mixed solvent in a mass ratio of (0.05~0.5):1, wherein the total mass of polyvinylpyrrolidone and 2-aminoterephthalic acid to the volume ratio of the solvent is (0.004~0.05):1 g / mL. After complete dissolution, add tetrabutyl titanate to a concentration of 0.01~0.2mol / L, continue stirring for 180 min, then transfer the solution to a Teflon liner and place it in an oven for hydrothermal reaction at 200~500℃ for 10~40 h. Collect the product by centrifugation and dry it to obtain NH2-MIL-125(Ti). S2. The dried NH2-MIL-125(Ti) was placed in a muffle furnace and calcined in air at 300~650℃ for 2~8 h to finally obtain the NH2-MIL-125(Ti)-derived TiO2 photocatalytic material, named TiO2-P.
2. The method for preparing the TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) according to claim 1, characterized in that, The drying process described in step S1 is vacuum drying at 60 °C for 8-12 h.
3. The method for preparing the TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) according to claim 1, characterized in that, In step S2, the heating rate of the muffle furnace is 1~10℃ / min.
4. A TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) prepared by the method described in any one of claims 1 to 3.
5. The application of the TiO2-P photocatalytic material derived from NH2-MIL-125(Ti) as described in claim 4 in the photocatalytic degradation of antibiotic-dye complex pollutants and ion coexisting pollutants in wastewater.